FusedOS: Fusing LWK Performance with FWK Functionality in a Heterogeneous Environment - Park, Yoonho; Hensbergen, Eric Van; Hillenbrand, Marius; Inglett, Todd; Rosenburg, Bryan; Ryu, Kyung Dong; Wisniewski, Robert W. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2012: Anais do XXIV International Symposium on Computer Architecture and High Performance Computing, 2012)
Traditionally, there have been two approaches to providing an operating environment for high performance computing (HPC). A Full-Weight Kernel(FWK) approach starts with a general-purpose operating system and strips it down to better scale up across more cores and out across larger clusters. A Light-Weight Kernel (LWK) approach starts with a new thin kernel code base and extends its functionality by adding more system services needed by applications. In both cases, the goal is to provide end-users with a scalable HPC operating environment with the functionality and services needed to reliably run their applications. To achieve this goal, we propose a new approach, called Fused OS, that combines the FWK and LWK approaches. Fused OS provides an infrastructure capable of partitioning the resources of a multicoreheterogeneous system and collaboratively running different operating environments on subsets of the cores and memory, without the use of a virtual machine monitor. With Fused OS, HPC applications can enjoy both the performance characteristics of an LWK and the rich functionality of an FWK through cross-core system service delegation. This paper presents the Fused OS architecture and a prototype implementation on Blue Gene/Q. The Fused OS prototype leverages Linux with small modifications as a FWK and implements a user-level LWK called Compute Library (CL) by leveraging CNK. We present CL performance results demonstrating low noise and show micro-benchmarks running with performance commensurate with that provided by CNK.